Coping and Work-Related Stress Reactions in Protective Services Workers. (25th June 2019) - Cummings, Caroline; Singer, Jonathan; Moody, Sarah A; Benuto, Lorraine T
Abstract: Burnout, secondary traumatic stress (STS) and vicarious trauma (VT) are three highly prevalent work-related stress reactions experienced in helping professions, but prevalence rates and protective/risk factors of these stress reactions in protective services workers have been understudied. The purpose of the current study was to examine coping mechanisms utilised by protective services workers and their relationship with the experience of burnout, STS and VT. Participants ( N  = 228) completed online measures of coping strategies and work-related stress reactions. Socially supported coping was the only adaptive coping skill that significantly predicted less burnout in protective service workers and none of the adaptive coping skills were associated with decreased STS or VT symptoms, suggesting that adaptive coping skills may not be effective enough to combat work-related stress reactions in protective services workers. Furthermore, child protective services (CPS) workers reported experiencing significantly more burnout, VT and STS symptoms than adult/elder protective services workers. Given the findings, there is a need for the testing of interventions that target increasing professionals' protective factors, especially CPS workers, for experiencing work-related stress reactions, rather than focusing solely on teaching and strengthening traditional coping skills, or addressing inconsistent risk factors.